2009
DOI: 10.1039/b902733e
|View full text |Cite
|
Sign up to set email alerts
|

A new stable CNHC⁁CH⁁CNHCN-heterocyclic dicarbene ligand: its mono- and dinuclear Ir(i) and Ir(i)–Rh(i) complexes

Abstract: The ligand [(1,3-phenylene)bis(methylene)]bis(1-ethyl-imidazol-2-ylidene) ( 2) (abbreviated as EtCNHC--CH--CNHC with CH = central aromatic ring, -- = CH2 spacer) has been synthesised, and isolated, by deprotonation of [(1,3-phenylene)bis(methylene)]bis(1-ethyl-imidazolium) dichloride, Et(CHimid.--CH--CHimid.)Cl2 ( 1) with LiN(SiMe3)2. This new, remarkably stable NHC dicarbene ligand is quantitatively protonated with HBr to form [(1,3-phenylene)bis(methylene)]bis(1-ethyl-imidazolium) dibromide Et(CHimid.--CH--C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…The mean C carbene ÀM distances of 206.0(3) pm (M = Rh) and 206(1)pm( M = Ir) are reasonably comparable to those found for otherN HC complexes of [M(cod)Cl]. [15][16][17] One striking feature is furthermore the bending of the structures ( Figure 3b), which is much more pronounced for 2h than 2a (absolutev alue of the averaged eviation from the plane defined by the central arene ring is 105.6 pm for 2a and 175.4 pm for 2h,r espectively).…”
Section: Synthetic Aspectssupporting
confidence: 71%
See 1 more Smart Citation
“…The mean C carbene ÀM distances of 206.0(3) pm (M = Rh) and 206(1)pm( M = Ir) are reasonably comparable to those found for otherN HC complexes of [M(cod)Cl]. [15][16][17] One striking feature is furthermore the bending of the structures ( Figure 3b), which is much more pronounced for 2h than 2a (absolutev alue of the averaged eviation from the plane defined by the central arene ring is 105.6 pm for 2a and 175.4 pm for 2h,r espectively).…”
Section: Synthetic Aspectssupporting
confidence: 71%
“…Nevertheless, both the absolutev alues of the 13 C(carbene) chemical shifts of 201.0 and 197.8 ppm for 2a and 2h,r espectively,a nd the 1 J( 103 Rh, 13 C) coupling constant of 49.1 Hz comparer easonably well with literature values. [15][16][17] The experimental UV/Vis spectra of 2a and 2h in CH 2 Cl 2 solution are similar ( Figure 4). Dominant transitions are observed at~33 000 cm À1 (e = 107 and 80 10 3 Lmol À1 cm À1 for 2a and 2h,r espectively)a nd~27 000 cm À1 (e = 56 and 80 10 3 Lmol À1 cm À1 for 2a and 2h,r espectively).…”
Section: Synthetic Aspectsmentioning
confidence: 71%
“…[8][9][10][11][12] Compared to the monodentate NHC ligands, polydentate NHC ligands, such as tripodal NHCs, showed the ability to bind multiple metal ions in a homometallic [13][14][15][16] or a heterometallic manner. [17] There are a few types of tridentate NHC ligands, as illustrated in Figure 1. The scorpion-162,000 h -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[42] In 1996, Herrmann and co-workerso btained af ree biscarbene from the relatedb is(azolium) salt with high yields by ar oute using liquid ammonia in anhydrous THF and sodium hydride. [43] As table biphenyl-biscarbene, [44] and a mxylene pincer bis(imidazolylidene) [45] were also obtained. In 2006, Bielawski et al reported the synthesis of the first Janustype biscarbene, benzobis(imidazolylidene), consisting of two diametrically opposed units of imidazol-2-ylidene attached to an arene backbone.…”
Section: Introductionmentioning
confidence: 97%
“…In 1996, Herrmann and co‐workers obtained a free biscarbene from the related bis(azolium) salt with high yields by a route using liquid ammonia in anhydrous THF and sodium hydride 43. A stable biphenyl‐biscarbene,44 and a m ‐xylene pincer bis(imidazolylidene)45 were also obtained. In 2006, Bielawski et al.…”
Section: Introductionmentioning
confidence: 99%